1973
DOI: 10.1038/bjc.1973.178
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Comparison Between Normal and Carcinomatous Squamous Epithelia of the Uterine Cervix

Abstract: Summary.-The object of this study was to measure some of the differences between normal squamous epithelial cells and cells from invasive squamous carcinoma of the uterine cervix. A total of 107 patients were studied; only those specimens which when assessed by a histopathologist were thought to show classic normal features or undoubted invasive carcinoma were included in the quantitative analysis. In addition, any specimens which at the electron microscope level, showed faulty sampling or preparation were dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1982
1982
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The reason for this increase is not well understood, but it is thought to be related to cell degeneration, as cellular debris can be observed in the enlarged spaces between cells (Sugar 1968). The one exception to this generally observed trend of increased ECS in abnormal tissue was reported by Wiernik et al (1973), who employed stereological techniques to analyse a number of tissue parameters in the basal part of fixed normal and carcinogenous cervical epithelium. In this case, a greater mean extracellular volume was observed in the normal controls than in the cancerous tissue.…”
Section: Extracellular Space (Ecs)mentioning
confidence: 98%
“…The reason for this increase is not well understood, but it is thought to be related to cell degeneration, as cellular debris can be observed in the enlarged spaces between cells (Sugar 1968). The one exception to this generally observed trend of increased ECS in abnormal tissue was reported by Wiernik et al (1973), who employed stereological techniques to analyse a number of tissue parameters in the basal part of fixed normal and carcinogenous cervical epithelium. In this case, a greater mean extracellular volume was observed in the normal controls than in the cancerous tissue.…”
Section: Extracellular Space (Ecs)mentioning
confidence: 98%
“…Certain morphometric analyses have concluded that a reduction in desmosomal number correlates with invasive behaviour (Alroy et al, 1981;Pauli et al, 1978;Schindler et al, 1981) while others have not substantiated this interpretation (Luzi et al, 1987;Wiernik et al, 1973). However, electron microscopical studies are necessarily based on small samples of tissue from each tumour and relatively small numbers of tumours.…”
mentioning
confidence: 99%
“…Such size distribution histograms may provide valuable information to characterize a population of, for example, nerve fibres by plotting the change in the size spectrum of their areas during the process of growth (Stanmore et al, 1978;Holland, 1978). Measurcments of nuclear size changes can be valuable when the development of malignancy is being studied (Wiernik et al, 1973) and measurements of alveolar wall thickness (Langston & Thurlbeck, 1978) are of interest to respiratory physiologists. Many other examples could be cited, some of which are referred to in the paper by Attle et al (1980) and in the earlier bibliography produced by Jesses (1974).…”
Section: Characterization B Y Size and Shapementioning
confidence: 99%